MANAJEMEN LOW VISION PADA ANAK USIA SEKOLAH - Zulhijjah Yati Syari (HUMAN CARE JOURNAL, 2021)
Low vision according to the World Health Organization (WHO) is a person who has impaired visual function after treatment or standard refraction correction and has visual acuity less than 6/18 (20/60) until the light perception or field of view is less than 100 from the fixation point and is still can use residual vision to perform certain activities. Low vision cases according to WHO is 3-4 times greater than cases of blindness. The prevalence of blindness in children varies from region to region or country, ranging from 0.15 to 1.5 per 1000 children. Of the 1.4 million children who are blind, 90% are in developing countries. In addition, there are 7 million low vision children. The prevalence of low vision in children is 11 times more than blindness in children. Low vision in children can be caused by eye abnormalities both congenitally and including cataracts, glaucoma, retinitis pigmentosa, clouding of the cornea, and retinopathy of prematurity (ROP). The clinical symptoms are blurred vision, limited field of view, accompanied by functional complaints such as decreased contrast sensitivity, glare, and color vision disorders so that visual aids are needed in low vision. Low vision examination consists of anamnesis, visual acuity measurement (examination of visus distance and close range), visual field examination, contrast sensitivity test, glare examination, and color blindness test. In this paper, we report cases of low vision in children where the management uses low vision aids according to their needs.Keywords: low vision, etiology, clinical symptoms, examination, low vision aids, management